Praktik Kepemimpinan Islam pada Organisasi Bisnis di Kota Gorontalo - Andi Mardiana (Al-Buhuts, 2016)
In applying the Islamic leadership in business organizations in the city of Gorontalo has a chance, because it is supported by the people of the city of Gorontalo Muslim majority, who have a philosophy in the local language " Adati Hulo-hulo’a syara’a, Syara’ a Hulo-hulo’a to Qur’ani "( adat bersendi syara’, Syarah bersendikan Kitabullah). Indigenous applied bersendikan on Islamic law and syariah-syariah adapted to customary widely applicable. Leadership is the formation of values, attitude and behavior is needed to motivate yourself and others. The impact of good leadership can build a relationship between leaders and followers to create values are aligned so that the impact on the achievement of corporate goals.